Durian Consumption Effect on the Plasma Malondialdehyde Level as Biomarker of Stress Oxidative in Rats - Anugrah Aulia Ulil Amri; Ani Melani Maskoen; Syarief Hidayat (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Excessive consumption of durian (Durio zibethinus Murray) in Indonesia is often connected with its effect on health. This study aims to understand the effect of durian consumption to malondialdehyde (MDA) in plasma as oxidative stress biomarker.Methods: The study used an experimental research design on animal models, in the Biochemistry and Molecular Biology Department, Faculty of Medicine, Universitas Indonesia, July–August 2012. Thirty two Sprague-Dawley rats were used, divided into four groups: control, treatment week 1, 2, and 3. Each treatment group was given 20 gram durian fruit diluted with water until 20 ml volume per oral, divided into two doses (10 ml each) with 4 hours interlude between doses for 1 week, 2 weeks, and 3 weeks. All groups got normal diet and water ad libitum. Plasma MDA level was measured by TBARS method, then analyzed using Kurskal-Wallis and Mann-Whitney tests.Results: Seventeen samples were successfully decapitated (5 for control; 6 for week 1; 3 for week 2; 3 for week 3). Average plasma MDA level for control treatment week 1, 2 and 3 groups were 0.707 nmol/ml, 0.432 nmol/ml, 0.312 nmol/ml, and 0.746 nmol/ml respectively. Data was significant (p<0.05) with p=0.02. Compared with control group, a significant increase occurred in week 1 and 2 groups with p=0.028 and p=0.025 respectively.Conclusions: Results of durian consumption show MDA level significantly decreases in week 1 and 2. However, MDA level dramatically increases exceeding control group level in week 3. [AMJ.2016;3(1):22–8] DOI: 10.15850/amj.v3n1.695